Acoustics and Vibration of Mechanical Structures-AVMS-2017 Proceedings of the 14th AVMS Conference, Timisoara, Romania, May 25-26, 2017 (Springer Proceedings in Physics,, 2018)
This book is a collection of papers presented at Acoustics and Vibration of Mechanical Structures 2017 - AVMS 2017 - highlighting the current trends and state-of-the-art developments in the field. It covers a broad range of topics, such as noise and vibration control, noise and vibration generation and propagation, the effects of noise and vibration, condition monitoring and vibration testing, modeling, prediction and simulation of noise and vibration, environmental and occupational noise and vibration, noise and vibration attenuators, as well as biomechanics and bioacoustics. The book also presents analytical, numerical and experimental techniques for evaluating linear and non-linear noise and vibration problems (including strong nonlinearity). It is primarily intended for academics, researchers and professionals, as well as PhD students in various fields of the acoustics and vibration of mechanical structures.